Kinerja perbankan BPR sebelum dan selama masa pandemi Covid-19 - Calvina Calvina; Miharni Tjokrosaputro (Universitas Tarumanagara, 2023)
During the Covid-19 pandemic, many economic sectors experienced significant disruption. This also has an impact on the banking sector, including BPR which are financial institutions that play a key role in supporting economic growth at the local level by providing banking services to the MSME sector. The purpose of this study was to examine the influence of Covid-19 on the financial performance of rural banks by determining whether there were differences before and during Covid-19. Quantitative research with a descriptive approach was employed for this study. The data used is secondary data derived from the publication of financial reports which can be accessed via the Financial Services Authority website with the data period 2018-2021. The financial performance ratios used are Capital Adequacy Ratio (CAR), Return on Assets (ROA), Return on Equity (ROE), Operational Income Operating Cost (BOPO), Net Interest Margin (NIM), Non-Performing Loan (NPL), Earning Assets Quality (KAP), Loan to Deposit Ratio (LDR), Cash ratio, and Current Ratio (CR). The data were processed using the Paired sample t-test and Wilcoxon signed-rank test using the EViews 12 application. The findings of this study show that bank performance from LDR has significant differences, while the performance of CAR, ROA, ROE, BOPO, NIM, NPL, KAP, Cash ratio, and CR did not exhibit significant differences before and during the pandemic. Banyak sektor ekonomi mengalami gangguan yang signifikan selama masa pandemi Covid-19. Hal ini juga berdampak pada sektor perbankan, termasuk BPR yang merupakan lembaga keuangan yang berperan penting dalam mendukung pertumbuhan ekonomi di tingkat lokal dengan menyediakan layanan perbankan kepada sektor UMKM. Penelitian ini bertujuan untuk meneliti apakah Covid-19 berdampak terhadap kinerja keuangan perbankan Bank Perkreditan Rakyat dengan membandingkan kinerja BPR sebelum dan selama pandemi. Jenis penelitian merupakan penelitian kuantitatif dengan pendekatan deskriptif. Data yang digunakan merupakan data sekunder yang berasal dari publikasi laporan keuangan yang dapat diakses melalui situs web Otoritas Jasa Keuangan dengan periode data tahun 2018-2021. Ada beberapa rasio kinerja keuangan yang digunakan antara lain Capital Adequacy Ratio (CAR), Return on Assets (ROA), Return on Equity (ROE), Operating Income Operating Cost (BOPO), Net Interest Margin (NIM), Non Performing Loan (NPL), Earning Assets Quality (KAP), Loan to Deposit Ratio (LDR), Cash Ratio, dan Current Ratio (CR). Data diolah dengan t-test paired sample dan tes ranking Wilcoxon dengan menggunakan aplikasi EViews 12. Penelitian ini menyimpulkan bahwa kinerja bank dari LDR mengalami perbedaan signifikan, sementara kinerja CAR, ROA, ROE, BOPO, NIM, NPL, KAP, Cash ratio, dan CR tidak mengalami perbedaan signifikan sebelum dan selama terjadinya pandemi.